Adapting to Thrive: Operation Management Capabilities and Flexibility Effects on Procurement Performance among Manufacturing Firms in Ghana - AGBEKA, Joseph Kwasi; KUMAH, Bismark Stephen; SENANU, Mawuli; AFRIFA JNR, Sampson (Management Dynamics in the Knowledge Economy, 2025)
This study examined the direct and moderating relationships between operational management capabilities, specifically process efficiency capability, process integration capability, operational flexibility and procurement performance among manufacturing firms in Ghana. The study adopted a quantitative cross-sectional survey design. A total of three hundred and fifty (350) procurement officials from fifty (50) manufacturing firms were selected for the study. Stratified and purposive sampling techniques were used in the selection of manufacturing firms and procurement officials, respectively. Questionnaires were used in the data collection, and data were analyzed using Partial Least Squares (PLS) Structural Equation Modelling (SEM). For direct effects, the study showed that a non-significant positive relationship exists between process integration capability and procurement performance. However, a significant positive relationship was found to exist between process efficiency capability and procurement performance. The study also found that operational flexibility does not moderate the relationship between process integration capability and procurement performance. Meanwhile, operational flexibility negatively moderates the relationship between process efficiency capability and procurement performance among manufacturing firms in Ghana. The results of the study highlight the importance of developing robust process efficiency capabilities for improved procurement outcomes, while also suggesting a careful balance in operational flexibility initiatives to avoid inefficiencies among manufacturing firms. The study contributes to the dynamic capabilities theory and provides practical implications for manufacturing firms seeking to optimize their procurement strategies.